The influence of a soccer season on non-contact injury and isokinetic peak torque of the quadriceps and hamstrings in professional youth soccer players - Brow, C. C.; Bakhshi, A.; Wrigely, R.; Dr Unnithan, V. B. (Research in Sports Medicine, 2021)
Isokinetic strength screening is utilized in professional soccer. However, there has been little research on the interaction between seasonal changes in players` peak torque (PT) and injury incidence. Twenty-five (age 16.5±0.68 years) professional youth soccer players participated in the study. Bilateral isokinetic concentric (CON) and eccentric (ECC) testing of Quadriceps (Q) and Hamstrings (H) were conducted at three time-points across the season. Absolute CON and ECC PT were measured at 60 degree/sec and in a supine 170-degree position. Testing data was normalized to body mass. A mixed design (2 by 3) repeated measures ANOVA with injury as a co-variate was conducted to evaluate the effect of season and/or limb dominance on PT and injury incidence. With regard to the seasonal variation and injury incidence, an interaction was identified with respect to non-dominant limb (NDL) QCON (p=0.01) and to a lesser extent the dominant limb (DL) QCON (p=0.05). The seasonal variation of the PT of the NDL QCON was different between the injured and non-injured individuals. Non-injured individuals, QCON strength increased over the course of the season. While for the Injured players, QCON declined from pre-season to mid-season then increased but never recovered to starting pre-season values.